FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS V SD NEGERI SAKTEO KECAMATAN MOLLO TENGAH KABUPATEN TTS - Markus Sampe; Maxsel Koro; Estherana Vilalina Tunliu (Journal of Character and ELementary Education, 2023)
The purpose of this study was to analyze the factors causing the low ability of students to read at SD Negeri Sakteo.This type of research is qualitative research.It is a research procedure that produces data and is descriptive in the form of written or spoken words and observable behavior. The research subjects were 5 students of class V (five), 1 class teacher, 1 school principal and 5 parents of class V students. Data collection is done by observation, interviews and documentation.The results of this study indicate that there are two factors that affect the low reading ability of fifth grade students at SD Negeri Sakteo, namely internal factors and external factors. Internal factors are caused by students' low interest in reading and students' lack of reading habits.External factors come from a less supportive school environment, limited books/reading materials, less optimal teacher role, and less supportive family environment.